Mastering Apache Maven. (Manning Publications, 2022)
This is a no-nonsense, demo-based introduction to getting started with Maven. You'll learn how to work with the Maven build tool, which is currently the number-one industry standard for creating Java applications. By concentrating on practical hands-on demonstrations, you'll see firsthand how Maven works. From there you will develop the skills--and the confidence--to use it on your own to build your Java projects at home, college, or in the workplace. While many video courses are delivered presentation style, this unique course uses a demonstration-first approach, explaining concepts through demonstration. You'll experience this approach first "at the command line," with videos showing what Maven is doing and explaining how it is doing it; then in IDEs using the sophisticated Maven integration that Eclipse and IntelliJ IDEA provide. In this way, you'll develop an understanding of the nuts and bolts of the tool and be in a position to develop effectively after the course is over. This approach also equips you with the "under the hood" understanding you need to effectively troubleshoot any problems you may encounter when developing with Maven on your own. Though this course has some useful content for people who are already using Maven, it is really intended for Maven beginners. Maybe you've started a new job where they use it to build their applications, or you're learning industry-standard tools to better place you ahead of the competition in the job market. By unlocking the mechanics of how Maven works in front of your eyes, the course will equip you to better build Java projects with the tool and have fun doing so.